Rac1 regulates interleukin 1-induced nuclear factor kappaB activation in an inhibitory protein kappaBalpha-independent manner by enhancing the ability of the p65 subunit to transactivate gene expression - O'NEILL, LUKE ANTHONY JOHN (American Society for Biochemistry and Molecular Biology, 2000)
We have examined the involvement of Rac1 in nuclear factor kappaB (NFkappaB) activation by interleukin 1 (IL1). IL1 induced a rapid and sustained activation of Rac1 in the thymoma cell line EL4.NOB-1. Transient transfection with dominant negative RacN17 inhibited IL1-induced kappaB-dependent reporter gene expression but not IkappaBalpha degradation, whereas constitutively active RacV12 potentiated kappaB-dependent reporter gene expression in response to IL1 but had no effects on its own. Using porcine aortic endothelial cells stably transfected with RacV12 or RacN17 under the control of an inducible promoter, we confirmed that RacV12 did not affect IkappaBalpha degradation, nor did RacN17 inhibit the IL1-induced response. RacV12 was also unable to induce nuclear translocation of NFkappaB. These effects suggested a role for Rac1 in p65-mediated transactivation of NFkappaB, independent of IkappaBalpha regulation. In support of this we found that IL1 activated a pathway leading to increased p65 transactivation activity and that RacV12 alone could drive this response in both cell systems. Additionally, RacN17 inhibited IL1-driven p65-mediated transactivation. From data using specific inhibitors of p38 and p42/p44 kinases we propose that both p38 and p42/p44 lie downstream of Rac1 on the IL1 pathway leading to enhanced transactivation by p65.
PUBLISHED
Keywords: Biochemistry